Prognostic potential of midregional pro‐adrenomedullin following decompensation for systolic heart failure: comparison with cardiac natriuretic peptides. (17th May 2017) - Morbach, Caroline; Marx, Almuth; Kaspar, Mathias; Güder, Gülmisal; Brenner, Susanne; Feldmann, Carolin; Störk, Stefan; Vollert, Jörn O.; Ertl, Georg; Angermann, Christiane E.; ,
Abstract: Aims: Whereas guidelines recommend the routine use of natriuretic peptides (NPs) in heart failure (HF) care, the clinical relevance and prognostic potential of midregional pro‐adrenomedullin (MR‐proADM) is less well established. We aimed to compare the prognostic potential of MR‐proADM after acute decompensation for systolic HF with that of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) and midregional pro‐atrial NP (MR‐proANP), to investigate the significance of high/rising MR‐proADM, and to evaluate the incremental prognostic yield of repeat measurements. Methods and results: The Interdisciplinary Network Heart Failure (INH) programme enrolled patients hospitalized for acute systolic HF and followed them for 18 months (100% complete). Of 1022 INH participants, 917 (68 ± 12 years, 28% female) who had biomaterials available were enrolled. High MR‐proADM was associated with more impaired left ventricular function, higher comorbidity burden, lower doses of HF medications, and lower likelihood of left ventricular reverse remodelling. Compared with NPs, MR‐proADM had superior prognostic significance (concordance index 0.72 for all‐cause mortality), improved Cox regression models including NPs ( P < 0.001), and was the only biomarker also predicting non‐cardiac death (hazard ratio 1.8 vs. 1.0). In the setting of low NPs, patients with high MR‐proADM experienced non‐cardiac death more often. Six month MR‐proADM enhanced models including baseline MR‐proADM ( P < 0.001) for prediction of all‐cause death (net reclassification index: 0.48, 95% confidence interval 0.19–0.78). Conclusion: MR‐proADM was found to correlate with the global disease burden in HF and proved a potent prognostic indicator, capturing the risk for both cardiac and non‐cardiac death. Serial MR‐proADM measurements further enhanced risk assessment, thus facilitating substantial reclassification.